Varanus mabitang, A RARE MONITOR LIZARD FROM PANAY ISLAND AND A NEW CONSERVATION TARGET - Gaulke, Maren; Curio, Eberhard; Demegillo, Arnold; Paulino, Narciso (Silliman Journal, 2022)
Despite its huge size (minimal total length of 175 cm), the Varanus mabitang became known to science only in 2001. According to present knowledge, this blackish, arboreal lizard is confined to forested areas of NW and W Panay. It has a vegetarian diet, consisting of fruits and leaves of different forest plants. Due to the restricted range and its specialized habits, the Mabitang is a threatened species. Its protection is directly correlated to the protection of its habitat.